2020
DOI: 10.1039/d0ra05845a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of saccharides on equilibrium swelling of thermo-responsive gels

Abstract: A model is developed for the mechanical response and equilibrium swelling of thermo-responsive gels and applied to the analysis of their volume phase transition in aqueous solutions of saccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…In the case of hydrogel network, increasing temperature above VPTT breaks the cage‐like structure of hydrophobic segments in polymeric chains, inducing the hydrogel to contract. This contraction of hydrogel also exemplifies hydrophobicity when heated 177 . Grunlan et al suggested a double network (DN) PNIPAAm hydrogel system to enhance thermosensitivity compared to a single network (SN) hydrogel without increasing the VPTT 66 .…”
Section: Stimuli‐responsive Deformation Of Pillar Arrays and Its Applicationsmentioning
confidence: 98%
“…In the case of hydrogel network, increasing temperature above VPTT breaks the cage‐like structure of hydrophobic segments in polymeric chains, inducing the hydrogel to contract. This contraction of hydrogel also exemplifies hydrophobicity when heated 177 . Grunlan et al suggested a double network (DN) PNIPAAm hydrogel system to enhance thermosensitivity compared to a single network (SN) hydrogel without increasing the VPTT 66 .…”
Section: Stimuli‐responsive Deformation Of Pillar Arrays and Its Applicationsmentioning
confidence: 98%
“…The list of cited works reports also theoretical papers where PDEs numerical methods and algorithms are described. The last type (type 3) of models is actually a large set of semi-empirical relationships available to correlate experimental data [25][26][27][28][29]. This approach appears intrinsically weak since it is not general based on first principles.…”
Section: Introductionmentioning
confidence: 99%
“…As such, they can be considered helpful tools to quickly identify peculiar system behaviours minimizing complexity. Their major strengths are (i) excellent reliability for specific applications, those for which they were tailored; (ii) easy implementation and (iii) quantitative results enabling data analysis at no Usually less detailed than type 1 but still first principle methods, hence also general but at lower degree of complexity (assumptions and empirical laws typically applied while ensuring enough accuracy) Computationally demanding (PDE have to be numerically solved; CFD commercial codes as well as ad hoc numerical methods are applied) [20][21][22][23][24] 3 Semi-empirical relationships tailored for specific cases; not general but versatile, flexible and non-time demanding; especially effective when limited experimental information is available; also useful to drive the experimental design Lack of generality [25][26][27][28][29][30] computational cost. Combined with a reasonable experimental campaign, these correlative models are well established and widely accepted in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is worth studying the specific effect of this biologically relevant sugar on the collapse of PNIPAM-based architectures. The PNIPAM-watertrehalose ternary system is much less investigated both experimentally and numerically as compared to any other ternary system of the same polymer, including those containing saccharides [44][45][46][47][48][49]. Experimental investigations using cloud point measurements, differential scanning and isothermal titration-microcalorimetry [44,46], report a significant decrease of LCST of PNIPAM chains in aqueous solution on increasing mono-and disaccharide concentration, finding a good correlation of the saccharide hydration with the decrease of LCST, and hence with the promotion of the globular compact state of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of saccharides has also been studied on another type of PNIPAM-based system, i.e. hydrogels, by evaluating the influence on the VPTT and swelling behavior, also in this case with a focus on the water-saccharide interactions [45,47,49]. To our best knowledge, however, only very few studies refer to trehalose.…”
Section: Introductionmentioning
confidence: 99%